2021
DOI: 10.1108/ijccsm-09-2020-0099
|View full text |Cite
|
Sign up to set email alerts
|

Socio-economic determinants of smallholder mixed crop-livestock farmers’ choice of climate change adaptation in the drylands of Northern Ethiopia

Abstract: Purpose This paper aims to understand the perception of smallholder farmers on climate change, identify major livestock related climate change adaptation (CCA) strategies and their determinants in selected neighboring districts of Tigray and Amhara regions of Ethiopia. Design/methodology/approach A total of 416 household heads were involved in a questionnaire survey using a multistage sampling approach. To understand the socio-economic factors that influence farmers’ perception on climate change (CC) and/or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
1
2
0
1
Order By: Relevance
“…This indicates that the higher the level of education pursued by farmers, the higher the likelihood of using this strategy. Similar findings were discovered by Menghistu et al (2021) who stated the level of education significantly influenced (p ≤ 0.05) the improvement of livestock feed. Both of these findings reaffirm that the education level of farmers is important to consider.…”
Section: Level Of Educationsupporting
confidence: 86%
“…This indicates that the higher the level of education pursued by farmers, the higher the likelihood of using this strategy. Similar findings were discovered by Menghistu et al (2021) who stated the level of education significantly influenced (p ≤ 0.05) the improvement of livestock feed. Both of these findings reaffirm that the education level of farmers is important to consider.…”
Section: Level Of Educationsupporting
confidence: 86%
“…This finding is in line with that of Belay et al (2017) who found that household size had a favorable and substantial effect on improved animal feed regime adoption. Menghistu et al (2021) concluded that larger households can draw on more diverse sources of knowledge in determining which feed regime is optimal to use for their livestock.…”
Section: Marginal Effectsmentioning
confidence: 99%
“…The aforementioned will result in a decrease in livestock production by 7.5%–9.6% which will cause an estimated economic loss of US$9.7–12.6bn. The multiplier effect of the foregoing will lead to an increase in livestock prices, a decrease in production and reduced income for those who depend on livestock farming for their sustenance and livelihoods (Simpkin et al , 2020; Menghistu et al , 2021).…”
Section: Introductionmentioning
confidence: 99%